Analisis Sistem Pengadaan Barang Operasional Pada Hotel Bukit Kenari di Parepare - Muhammad Anas; Murdiani Sukarana; Andri Machmury (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2020)
The procurement system for operational goods at the Bukit Kenari Hotel in Parepare is the focus of this research. The objectives of this study are: 1). Analyzes the operational goods procurement system at the Bukit Kenari Hotel in Parepare. 2). Explain the administrative procedures for the procurement of operational goods at the Bukit Kenari Hotel in Parepare. This type of research is qualitative using observation and interview data collection techniques. The results of the study indicate that the operational goods procurement system at Bukit Kenari Hotel in Parepare uses several systems including the use of a Contract System for several types of beverages, the Daily System for goods needed regularly, especially in the kitchen, and the monthly procurement system held with cash purchases. Then the administrative procedures for procurement of operational goods at the Bukit Kenari Hotel in Parepare include: filling out the request form, then signed by the head of office (head office), then signed by the operational manager and finally the form is submitted to the procurement department as a basis for buying goods needed by user.